Surfing the right ventricular pressure waveform: methods to assess global, systolic and diastolic RV function from a clinical right heart catheterization - Vanderpool, Rebecca R. (Pulm Circ, 2020)
Right ventricular (RV) function strongly associates with mortality in patients with pulmonary arterial hypertension (PAH). Current methods to determine RV function require temporal measurements of pressure and volume. The aim of the study was to investigate the feasibility of using right heart catheterization (RHC) measurements to estimate systolic and diastolic RV function. RV pressure and volume points were fit to P = α(e(βV)-1) to assess diastolic stiffness coefficient (β) and end-diastolic elastance (Eed). Single-beat methods were used to assess RV contractility (Ees). The effects of a non-zero unstressed RV volume (V(0)), RHC-derived stroke volume (SV(RHC)), and normalization of the end-diastolic volume (EDV) on estimates of β, Eed, and Ees were tested using Bland–Altman analysis in an incident PAH cohort (n = 32) that had both a RHC and cardiac magnetic resonance (CMR) test. RHC-derived measures of RV function were used to detect the effect of prostacyclin therapy in an incident PAH cohort and the severity of PAH in prevalent PAH (n = 21). A non-zero V(0) had a minimal effect on β with a small bias and limits of agreement (LOA). Stroke volume (SV) significantly influenced estimates of β and Ees with a large LOA. Normalization of EDV had minimal effect on both β and Eed. RHC-derived β and Eed increased due to the severity of PAH and decreased due to three months of prostacyclin therapy. It is feasible to detect therapeutic changes in specific stiffness and elastic properties of the RV from signal-beat pressure-volume loops by using RHC-derived SV and normalizing RV EDV.